Kiln-Drying of Lumber - Keey, Roger B.; Langrish, Timothy A. G.; Walker, John C. F. (Springer Series in Wood Science, 2000)
At present, no single book adequately covers a basic understanding of wood book satisfies the need for such a work. It describes drying in practice. This the fundamental basis of kiln-drying technology, to enable forest companies to imFrove their drying operations as high-quality timbers become scarcer and of yesteryear can no longer be tolerated. Adaptive the wasteful practices is no longer good enough. Innovations change based on past experience of the material being dried and the processes require a sound understanding of drying. Newer techniques, such as the use of ultrahigh temperature sea soning and superheated steam under vacuum, require an even greater depth of physical understanding for these methods to be used effectively and economically. book provides a description of modern ideas about wood structure, This moisture movement and stress development, from which models of the drying process are developed to give the kiln operator important information about the course of drying under specified conditions, and thus a means is compared with practice wherever for rational process improvement. Theory possible